Analisis Pengelolaan Aset Daerah Pada Badan Pengelolaan Keuangan Dan Aset Daerah (BPKAD) Provinsi Sumatera Utara - Lismaini Agustin; Azhari Akmal Tarigan (LPPM IAI Nasional Laa Roiba Bogor, 2022)
Assets are all assets/wealth owned by a person or business, both tangible and intangible, whose value or value will provide future benefits for every person or business. The management of regional assets must be managed properly so that these assets can become a source of funds for local governments to develop their capacity. This study aims to determine the description of Asset Management of the Regional Property Financing Agency (BPKAD) of North Sumatra Province. As a regional finance officer (treasury), BPKAD is a technical service that carries out its mission to obtain regional revenues and direct funds for regional needs through regional finance. This research is a qualitative descriptive research. Gain an in-depth understanding of various aspects related to the object of research. The method used for data collection is through observation, interviews, literature studies, documents, and internet searches. Finally, this research can be concluded that the management of fixed/regional goods carried out by the real estate sector in the North Sumatra Province BPKAD has been carried out properly and has been in accordance with Permendagri No.19 of 2016 concerning guidelines for managing regional property, but all have not been realized. Keywords: Asset Management, BPKAD, North Sumatra